The Influence of Work Motivation and Job Satisfaction on Teacher Performance Yayasan Dharma Setia Kosgoro Kota Bogor - Elbie Yudha Pratama; Dian Indiyati; Ratri Wahyuningtyas (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2026)
Dharma Setia Kosgoro Bogor City Foundation (YDSK) is an educational foundation established in 1987 that oversees three educational units, namely SMP Kosgoro, SMA Kosgoro, and SMK Kosgoro. As a private educational institution, the foundation faces challenges related to the uneven performance of teachers across its three educational units. An analysis of the Teacher Performance Assessment (PKG) document for the 2020/2021 academic year revealed an average score of 91.07%, categorized as